Assessment of Moisture Susceptibility of Hot Asphalt Mixtures Sustainable by RCA and Waste Polypropylene - Abdulghafour, Maha Mohammed; Ismael, Mohammed Q. (Engineering, Technology & Applied Science Research, 2024)
Sustainability plays an integral role in ensuring the continued existence of life on Earth and the protection of the natural environment. The recycling process is one of the most significant methods through which this strategy can be implemented. The potential environmental benefits of recycled concrete aggregates and polymer waste have attracted considerable interest within the asphalt industry. The present study focuses on the recycling of two materials to create asphalt mixtures. The first of these is polypropylene, which is mixed with asphalt cement at weight rates of 2%, 4%, and 6%. The second is treated and untreated Recycled Concrete Aggregate (RCA), which is substituted with coarse aggregate at weight rates of 20%, 40%, and 60%. The experimental work comprised the identification of the optimum asphalt content through the utilization of the Marshall design approach, the assessment of Marshall and volumetric characteristics, and the evaluation of moisture susceptibility through the measurement of Indirect Tensile Strength (ITS) and compressive strength. The findings indicated that all mixtures containing recycled polypropylene polymers and treated/untreated RCA exhibited a higher Tensile Strength Ratio (TSR) of approximately 6.1-14.7% and compressive strength of approximately 3.1-17.6% compared to control asphalt mixtures. This suggests that the mixture’s resilience against moisture damage has been enhanced.